PERBEDAAN HASIL BELAJAR IPS ANTARA TIPE KEPRIBADIAN INTROVERT DAN EKSTROVERT DI KELAS V SD NEGERI 110 PEKANBARU - Septiani, Ayzus; Noviana, Eddy; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to see whether there are differences in IPS learning outcomes between introvert and extroverted personality types in class V SD Negeri 110 Pekanbaru. In this research using Sample Sampling technique on sampling of 107 students. Research instrument of collecting data in the form of questionnaire that has been validated by validator and documentation. After done the data processing questionnaire introvert and extrovert personality types then got students who have introverted personality as much as 26 students while extrovert personality as much as 67 people and for students who balance as many as 14 people. From the analysis of learning outcomes obtained the average of introvert personality type 72.88 and extrovert 75.08. From the normality test for introverted personality type, amax value (0.038) < Dtabel (0,266), then H0 accepted means that the data of introvert personality type is normally distributed. And the extroverted personality data type is obtained by amax value (0.018) < Dtabel (0,166), then H0 is accepted means the data of introvert personality type is normally distributed. From the data above obtained that the data introvert and extrovert personality types are normally distributed. After doing the normality test the researchers conducted homogeneity test. After the homogeneity test data obtained value Fhitung (0.038) < Ftabel (1.48), then H0 accepted means the data has a homogeneous variance. Based on t test results obtained t hitung (0.621) < t tabel (1.644), then H0 accepted means there is a difference between learning results IPS introvert personality type and extrovert. Where extroverted learning outcomes are higher than introverted learning outcomes.Keywords: Introverted and Ekstroverted Personality Type, Learning Outcomes IPS.